Scottish football - Morrow, S. (Journal of Sports Economics, 2006)
The past few years have been financially challenging for Scottish football clubs: sustained losses, record levels of indebtedness, and several clubs placed in administration. There are numerous reasons why Scottish football finds itself in this state. External factors such as changes in the economics of football, in particular changes in football's relationship with broadcasters, have contributed; so have internal factors such as poor financial management. Although the need to adopt decision-making and control procedures appropriate to the present financial circumstances of Scottish football is recognized, there is also a need for structural reform at both the domestic and European levels.